Marriage and marriageability : the practices of matchmaking between men from Japan and women from Northeast China - Yamaura, Chigusa, 1977- (Cornell University Press, 2020)
"This book asks what makes one marriageable by examining the practices of brokered cross-border marriages between Japan and northeastern China"--Provided by publisher.